HOUSEHOLDS’ OVER-INDEBTEDNESS: AN EXPLANATION FROM A SHARI‘AH PERSPECTIVE - Ghaouri, Mohamed Hamza; Kassim, Salina; Zakariyah, Habeebullah; Abdullah Othman, Anwar Hasan (Jurnal Syariah, 2023)
Excessive indebtedness at the individual level can create vulnerability to exploitation (Zulm), leading to a modern form of slavery known as debt bondage. Household over-indebtedness has become an increasingly widespread phenomenon in Malaysia, compounded by the negative economic impact of the COVID-19 pandemic. In response, this study explores the different aspects of indebtedness from a Sharī‘ah perspective. The research draws on a qualitative methodology, including an intensive literature review, analysis of Quranic verses and the sayings of the Prophet. (pbuh), as well as interviews with reputable scholars. The study provides a detailed understanding of Sharī‘ah’s position on debt in various circumstances, the relationship between debtors and creditors, preventive solutions, and solutions for those over-indebted. The study highlights rules that regulate the relationship between debtors and creditors and suggests solutions to assist households in financial difficulties. The study concludes that incurring debt should be for Sharī‘ah-compliant purposes and with a genuine intention to pay back, regardless of the hierarchy of needs. This study makes a valuable contribution to the literature on preventing debt bondage and offers insights that can help households avoid over-indebtedness.